Pemodelan Matematika SITRS Penyebaran Pengguna Narkoba dengan Treatment - Fathiya Putri Dayustin; Media Rosha (UNIVERSITAS NEGERI PADANG, 2021)
Abstract－Drugs are compounds that can affect the brain's functioning system. To slow the spread of drug users, which continues to rise, holistic treatment is used. The goal of this study was to determine the form of the SITRS mathematical model of drug user distribution by treatment and to interpret the results of the analysis of the SITRS mathematical model on drug user distribution by treatment. This is a fundamental or theoretical study. The human population is divided into four population groups in the development of a mathematical model: susceptible, infected, treatment, and removed. According to the model analysis, there are one equilibrium point free of drug users and one endemic equilibrium point with treatment for drug users. The stability analysis of the system resulted in a basic reproduction ratio of 0,1751824818 for the equilibrium point free and 4,61528461 for the endemic equilibrium point. Stability using eigenvalue criteria. The results obtained by each individual who becomes a drug user when receiving treatment on a regular basis can help to reduce the spread of drug users.